Demokrasi Islam dalam Pandangan Muhammad Natsir dan Muhammad Abid Al-Jabiri - Tomi Agustian (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2020)
Muhammad Natsir is an Indonesian thinker and politician, including those who take note. He prefers to combine the concept of Western democracy with Islamic values, thus bringing up the concept of theistic democracy. While on the other hand there is Muhammad Abid al-Jabiri who feels that democracy is a 'necessity' for every nation. The argument he built was not because of the compatibility between democracy and Islam, but rather because of the reality faced by the Arabs. Natsir and al-Jabiri were religious nationalists who fought for democracy. Because this research is a study of the history of thought, the approach used is a socio-historical approach, which is an approach used to determine the socio-cultural and socio-political background of a character, because the thought of a character is the result of interaction with the environment. Natsir uses the reconstruction method while al-Jabiri uses the deconstruction method. Both are included in the category of reformistic typology thinkers, namely those who believe that turâŝ and modernity are both good. Therefore, trying to harmonize tour and modernity by not violating common sense and rational standards.